A nephron model for study of drug-induced acute kidney injury and assessment of drug-induced nephrotoxicity. (February 2018) - Qu, Yueyang; An, Fan; Luo, Yong; Lu, Yao; Liu, Tingjiao; Zhao, Weijie; Lin, Bingcheng
Abstract: In this study, we developed a multilayer microfluidic device to simulate nephron, which was formed by "glomerulus", "Bowman's capsule", "proximal tubular lumen" and "peritubular capillary". In this microdevice, artificial renal blood flow was circulating and glomerular filtrate flow was single passing through, mimicking the behavior of a nephron. In this dynamic artificial nephron, we observed typical renal physiology, including the glomerular size-selective barrier, glomerular basement membrane charge-selective barrier, glucose reabsorption and para-aminohippuric acid secretion. To demonstrate the capability of our microdevice, we used it to investigate the pathophysiology of drug-induced acute kidney injury (AKI) and give assessment of drug-induced nephrotoxicity, with cisplatin and doxorubicin as model drugs. In the experiment, we loaded the doxorubicin or cisplatin in the "renal blood flow", recorded the injury of primary glomerular endothelial cells, podocytes, tubular epithelial cells and peritubular endothelial cells by fluorescence imaging, and identified the time-dependence, dose-dependence and the death order of four types of renal cells. Then by measuring multiple biomarkers, including E-cadherin, VEGF, VCAM-1, Nephrin, and ZO-1, we studied the mechanism of cell injuries caused by doxorubicin or cisplatin. Also, we investigated the effect of BSA in the "renal blood flow" on doxorubicin-or-cisplatin-induced nephrotoxicity, and found that BSA enhanced the tight junctions between cells and eased cisplatin-induced nephrotoxicity. In addition, we compared the nephron model and traditional tubule models for assessment of drug-induced nephrotoxicity. And it can be inferred that our biomimetic microdevice simulated the complex, dynamic microenvironment of nephron, yielded abundant information about drug-induced-AKI at the preclinical stage, boosted the drug safety evaluation, and provided a reliable reference for clinical therapy.